2019
DOI: 10.3390/app9245447
|View full text |Cite
|
Sign up to set email alerts
|

Child’s Target Height Prediction Evolution

Abstract: This study is a contribution for the improvement of healthcare in children and in society generally. This study aims to predict children's height when they become adults, also known as "target height", to allow for a better growth assessment and more personalized healthcare. The existing literature describes some existing prediction methods, based on longitudinal population studies and statistical techniques, which with few information resources, are able to produce acceptable results. The challenge of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…In boys the average prediction error of the XBG method was around 3 mm larger than of the GCC method, but this difference declined towards adult height. Our identified prediction errors of this method were, nevertheless, much smaller than the reported errors in a study utilizing parental height [ 34 ], which reported almost 60 mm prediction error.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In boys the average prediction error of the XBG method was around 3 mm larger than of the GCC method, but this difference declined towards adult height. Our identified prediction errors of this method were, nevertheless, much smaller than the reported errors in a study utilizing parental height [ 34 ], which reported almost 60 mm prediction error.…”
Section: Discussioncontrasting
confidence: 74%
“…Another recent study by Rativa et al [ 32 ] used support vector regression, Gaussian process regression and artificial neural networks, to estimate height and weight from anthropometric measurements. Both aforementioned studies predicted height of the already adult individuals and their results could be used in forensics, textile technology, security and health care, but it wasn’t until recently that the first attempts to use ML for adult height prediction of children from childhood height [ 33 ] or parental height [ 34 ] were published.…”
Section: Introductionmentioning
confidence: 99%
“…Sunghyeon Choi forecasted solar energy output by employing RF, XGBoost, and LightGBM models [ 26 ]. Moreover, J.Cordeiro, O. Postolache, and J. Ferreira used the XGBoost model and the LightGBM model to predict the height of children [ 27 ]. Accordingly, in the modeling phase, we adopted the XGBoost and LightGBM to have the benefits of the features of our PAN-LDA model.…”
Section: Related Workmentioning
confidence: 99%
“… Reference Year Base model Time series prediction Data set [ 28 ] 2021 SVM, LR, Multi-layer perceptron, RF Covid-19 pandemic cumulative case forecasting Data of COVID-19 between January 20, 2020, and September 18, 2020, for the USA, Germany, and global was obtained from the World Health Organization website. [ 17 ] 2020 LR, SVM, ANN, RF, XGBoost, LightGBM Prediction of peak demand days of cardiovascular disease(CVD) admissions Health Information Center of Sichuan Province, China: the daily number of admissions of CVD patients in hospital Chengdu Meteorological Monitoring Database: Meteorological data China National Environmental Monitoring Cente: air pollutants data [ 25 ] 2020 XGBoost, CatBoost, LightGBM Prediction of problems in data mining of credit scoring domain Home Credit Default Risk from Kaggle Challenge [ 26 ] 2020 RF, XGBoost, LightGBM Photovoltaic Forecasting Data of a Photovoltaic plant in South Korea [ 18 ] 2020 LightGBM Cryptocurrency price trend Daily trading data from https://www.investing.com/ [ 29 ] 2020 XGBoost, ARIMA Hemorrhagic fever with renal syndrome Monthly hemorrhagic fever with renal syndrome incidence data from 2004 to 2018 from the official website of the National Health Commission of the People's Republic of China [ 27 ] …”
Section: Related Workmentioning
confidence: 99%
“…Recently, there is an approach using height data and machine learning techniques [25][26][27]. The study [25] analyze Galton's height data and predict adult height using various machine learning techniques. The author of this study is plan of further analysis by adding features and using cohort data.…”
Section: Introductionmentioning
confidence: 99%